Un populisme de la misère : Haïti sous la présidence Aristide (1990-2004) - Laurent Jalabert (Amnis)
Jean-Bertrand Aristide was elected in 1990 resulting from a great popular movement in his favour in which he stated he wanted to transform his country from unworthy « misery to worthy poverty ». He left his country in 2004, 3 years after a disputed re-election, leaving Haiti in a deteriorated economic and social situation. His way of governing is assimilated to a « modern populism » which was slowly set up in the context of a dubious democratic transition. Modern populist, he uses all means to remain in power: corruption, militia of fanatical young people, demonisation of the Western countries, exhortation of the people… He also called upon the usual methods of populist leader: ruling the society by terror, the media, the party, electoral fraud, and corruption…. His failure is caused by the limits of his support (uncontrollable armed militia, uncertain role and weights of the drug Mafia, internal division in his own party, weakness of the police force, absence of army, international isolation). In this context, in spite of the terror imposed on intellectuals and opposition, he did not manage to prevent powerful dissatisfactions to rise. The people, manipulated, did no longer believe in their President as of the years 2002-2003. Brought to power by the populations of the shantytowns, Aristide fell short on their expectations. He had put himself in the shoes of a populist without imagination. He had failed in all fields, sinking into demagoguery and speeches without effect on the opinion. The regime of Aristide was only populism of unworthy misery for a worthy nation still seeking for democracy.